(untitled) (Scientific journal of the Fergana State University, 2026)
This study examines the impact of self-efficacy on improving writing skills in foreign language instruction, focusing on a cohort of 95 undergraduate students from the English Language and Literature Faculty at Fergana State University. Self-efficacy, defined as one’s belief in their ability to achieve specific outcomes, plays a crucial role in language acquisition, particularly in enhancing writing proficiency. Through a mixed-methods approach, this research explores the relationship between students’ self-efficacy beliefs and their writing performance. The findings suggest that higher levels of self-efficacy correlate with improved writing skills, highlighting the importance of fostering self-efficacy in language learners to enhance their academic performance. This study contributes to the understanding of the psychological factors influencing language learning and provides insights for educators seeking to improve student outcomes.